Influence of website attributes on consumer's online purchase intention in Malaysia - Omoloju, Mariam Adedoja (2023)
Website user behaviour has been the subject of numerous studies since the inception of the interactive internet. Researchers have examined visitors’ actions on a website, including where and what they click on, how they scroll down a page, pause interactions, or act, and where they eventually drop off the page and leave. With the growth of internet usage, website owners have attempted to create compelling and interactive sites that encourage user adoption. Specifically, e-commerce websites have gained popularity due to their impact on business revenues. This study focuses on e-commerce websites to interrogate the attributes that drive consumer behaviour. While the subject has been widely studied, the dynamic nature of e-commerce and user behaviour means that there are still unexplored aspects of consumer behaviour that require further examination. In addition, previous studies have assumed equal importance of e-commerce website attributes, whereas this study sought to interrogate the weight of one characteristic relative to the others. This study was conducted to investigate the influence of e-commerce website attributes on consumer online purchase behaviour under four objectives. First, the study explored the influence of website convenience on consumer online purchase intention. Second, the researcher analysed the influence of website speed on consumer online purchase intention. Third, the study investigated the effect of website design on consumer online purchase intention and, finally, the influence of website security on the purchase intention of consumers. Prior to data collection, the researcher piloted 30 students to validate the survey instrument. Following instrument validation, the primary data were collected via a structured questionnaire distributed online using Google Forms. The survey targeted e-commerce platform users in Malaysia, and the researcher generated a contact list of users from various e-commerce platforms, social media, communities, and peer groups. The survey collected data from 384 online consumers, and the data were analysed using the Statistical Package for the Social Sciences v.25 software. Descriptive, correlation and regression analyses were conducted to analyse the data. The regression analysis revealed that website convenience, speed, design, and security positively influenced consumer online purchase intention, thereby supporting all four hypotheses. However, website design emerged as the most influential factor among all four attributes, having the highest correlation. The study is unique in its ability to determine the weight of one website attribute relative to the other attributes in influencing the online purchase intention of consumers. In the correlational analysis, the P value was used to determine the weight of association among all attributes and identify the most significant one. Both the regression and correlation results indicated that website design is the most significant attribute influencing consumer’s intention to make purchases on a website. This finding implies that website managers should prioritise the interface of their website, including its structure and content. However, web developers should also ensure that the websites provide maximum convenience, with easy and fast clicks, as well as being well-secured websites for the safety and privacy of their users, as these website attributes were also found to positively influence the intention of consumers to purchase via a website. Overall, the study has findings with implications of ecommerce websites for retailers in marketing to consumers and their influence on the consumer purchase decision-making process. Additionally, this study extends the research on the weighting of various factors in creating an impactful website, whereas previous studies mostly focused on critical attributes but did not make critical comparisons among them. This research is limited to respondents from known platforms accessible to the researcher. Therefore, the study may not be representative of total users of e-commerce platforms in Malaysia.